Associations between Family Functioning, Emotion Regulation, Social Support, and Self-injury among Emerging Adult University Students - Boyes, Mark; Mah, M.A.; Hasking, Penelope (SPRINGER, 2023)
We tested whether difficulties in emotion regulation mediated the association between family functioning and non-suicidal self-injury (NSSI), and whether associations between family functioning, emotion regulation, and NSSI were moderated by social support. University students (N = 846, 75.8% female, 35.5% with a history of NSSI, Mage = 20.76) completed an online questionnaire including well-validated measures of family functioning, emotion regulation, social support, and NSSI. Poor family functioning was positively associated with history of NSSI, but not past 12-month frequency of NSSI. Difficulties in emotion regulation were positively associated with both history of NSSI and frequency of NSSI in the past 12 months. Social support from friends moderated the relationship between difficulties in emotion regulation and history of NSSI; the association was stronger at higher levels of support. Poor family functioning had an indirect effect on both history of NSSI and frequency of NSSI via difficulties in emotion regulation; however, for frequency the indirect effect was only observed when social support from friends and significant others were low. Poor family functioning, difficulties in emotion regulation, and social support work together to predict NSSI engagement among university students. Findings inform potential integration of current theories and design of targeted interventions.